Paul Valéry: exchange, fiducia and myth. Three ideas for a theory of the social world - Ramírez Jaramillo, John Fredy (Estudios de Filosofía, 2018)
The aim of this paper is to show that Paul Valéry’s thought encompasses the essential traces of a philosophy attentive to the study of the factors that determine the emergence of the social world. In order to do so, it will examine three ideas that the French author deploys to interpret the functioning of life both at the individual and collective levels. The first is the idea of exchange, which serves to clarify how the processes of social exchange are regulated by a principle of inequality. The second is the idea of fiducia. This notion shows the importance of belief as a mechanism of social cohesion that is also linked to language. The third is the idea of myth, which serves to think about the need that we have to define a substantial part of our life from the vague, the speculative and the imaginative.